Analisis SWOT Dalam Strategi Pengembangan UMKM Pada Rumah Produksi Keripik Ubi Olis Kota Jambi: Penerapan Strategi Pengembangan UMKM Menggunakan Analisis SWOT - Yuni Hayati; Habriyanto Habriyanto; Fauzan Ramli (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2024)
This research aims to determine a good strategy to determine strengths, weaknesses, opportunities and threats. SWOT analysis is used to obtain information from analysis of the company's internal and external environment. This analysis is very important for the development of UMKM for sweet potato chips. And to find out the implementation of the strategy for developing UMKM for sweet potato chips in Jambi City. The method used is qualitative, where the research analyzes and describes the findings through observation, interviews and documentation. The data sources used are primary and secondary data, as well as data validity techniques using Tringulation. The results of this research are: expanding distribution locations, implementing prices according to quality, additional product variants, and carrying out promotions. And it is important for UMKM for sweet potato chips to prepare themselves to be able to compete with large businesses, as well as formulating marketing strategies regularly to remain competitive in a changing market. for a SWOT analysis of (UMKM) Jambi City's Olis Sweet Potato Chips Production House which is still below its competitors like in other places, this can be seen from the strategies used by Olis Sweet Potato Chips UMKM entrepreneurs regarding the situation or external and internal factors of UMKM entrepreneurs Olis Sweet Potato Chips are taken from the results of weighting the total existing values.